Laparoscopic and natural orifice transluminal restorative proctocolectomy: no abdominal incision for specimen extraction or ileostomy - Cuneyt Kayaalp; Mehmet Ali Yagci; Vural Soyer (Videosurgery and Other Miniinvasive Techniques)
The aim of this study was to demonstrate the feasibility of laparoscopic restorative proctocolectomy (LRPC) without additional abdominal incisions. Two sisters with familial adenomatous polyposis were enrolled. The colon and rectum were mobilized entirely through the five abdominal trocars. The terminal ileum and distal rectum were transected with endoscopic staplers. The entire colorectal specimen was extracted transanally. A circular stapler anvil was introduced transanally. The J-pouch was created intracorporeally. The rectal stump was re-closed and a pouch-anal anastomosis was created using a circular stapler. We used a transanal tube for decompression of the pouch instead of a diverting ileostomy. The patients were discharged on the 10th and 12th days uneventfully. Both were doing well with their pouches after 18.5 and 12.1 months of follow-up. With the help of transanal specimen extraction and transanal tube decompression, additional abdominal incisions can be avoided following LRPC.